Experimental Evaluation of the Impact of Intrinsic Process Parameters on the Performance of a Continuous Chromatographic Polishing Unit (MCSGP). Issue 7 (2nd May 2019) - Vogg, Sebastian; Ulmer, Nicole; Souquet, Jonathan; Broly, Hervé; Morbidelli, Massimo
Abstract : The semicontinuous twin‐column multicolumn countercurrent solvent gradient purification (MCSGP) process improves the trade‐off between purity and yield encountered in traditional batch chromatography, while its complexity, in terms of hardware requirements and process design, is reduced in comparison to process variants using more columns. In this study, the MCSGP process is experimentally characterized, specifically with respect to its unique degrees of freedom, i.e., the four switching times, which alternate the columns between interconnected and batch states. By means of isolation of the main charge isoform of an antibody, it is shown that purity is determined by the selection of the product collection window with negligible influence from the recycle phases. In addition, the amount of weak and strong impurities can be specifically attributed to the start and end of the collection, respectively. Due to higher abundance of weakly adsorbing impurities, the start of product collection influences productivity and yield more than the other switching times. Furthermore, most of the encountered tendencies scale between different loadings. The found trends can be rationalized from the corresponding batch chromatogram and therefore used during process design to obtain desirable process performances without extensive trial‐and‐error experimentation or complete model development and calibration. Abstract : The multicolumn countercurrent solvent gradient purification (MCSGP) process allows the alleviation of the purity–yield–trade‐off encountered in batch bind‐elute chromatography. In this study, the four switching times indicating the alternation of the two columns between interconnected and batch states are systematically varied to elucidate their impact on the process outcome. This work increases the understanding of the MCSGP process and can therefore reduce laborious trial‐and‐error experimentation during process development.